2012
DOI: 10.1111/j.1360-0443.2012.04021.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐harm, substance use and psychological distress in the Australian general population

Abstract: Aims To examine predictors of self‐harm, especially substance use and psychological distress, in an Australian adult general population sample. Design Sequential‐cohort design with follow‐up every four years. Setting Australian general population. Participants A random sample of adults aged 20–24 and 40–44 years (at baseline) living in and around the Australian Capital Territory. Measurements Self‐report survey including items on four common forms of self‐harm. Psychological distress was indexed by the combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 64 publications
(82 reference statements)
5
19
1
Order By: Relevance
“…We hypothesized that abuse history, as opposed to gender, would predict both forms of self-harm. Our results support this hypothesis and replicate other findings that suggest that abuse history is an important factor in self-harm (Boudewyn & Liem, 1995;Briere & Gil, 1998;Ford & Gómez, in press;Glassman et al, 2007;Gómez & Freyd, 2013;Gratz, 2006;Gratz et al, 2002;Hilt et al, 2008;Maniglio, 2011;Moller et al, 2013;Nock, 2012;Rabinovitch, Kerr, Leve, & Chamberlain, 2014;Swannell et al, 2012;Wedig et al, 2012;Zlotnick et al, 1996). Consistent with some other studies (e.g., Guan et al, 2012), we found that gender alone was not a predictor of selfharm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We hypothesized that abuse history, as opposed to gender, would predict both forms of self-harm. Our results support this hypothesis and replicate other findings that suggest that abuse history is an important factor in self-harm (Boudewyn & Liem, 1995;Briere & Gil, 1998;Ford & Gómez, in press;Glassman et al, 2007;Gómez & Freyd, 2013;Gratz, 2006;Gratz et al, 2002;Hilt et al, 2008;Maniglio, 2011;Moller et al, 2013;Nock, 2012;Rabinovitch, Kerr, Leve, & Chamberlain, 2014;Swannell et al, 2012;Wedig et al, 2012;Zlotnick et al, 1996). Consistent with some other studies (e.g., Guan et al, 2012), we found that gender alone was not a predictor of selfharm.…”
Section: Discussionsupporting
confidence: 92%
“…In childhood, physical abuse, emotional abuse, sexual abuse, and peer victimization have all been associated with self-harm directly, and with difficulty in managing emotional states and social relationships that could lead to self-harm (Boudewyn & Liem, 1995;Briere & Gil, 1998;Glassman, Weierich, Hooley, Deliberto, & Nock, 2007;Gratz, 2006;Gratz, Conrad, & Roemer, 2002;Hilt, Cha, & Nolen-Hoeksema, 2008;Maniglio, 2011;Moller, Tait, & Byrne, 2013;Wedig et al, 2012;Zlotnick et al, 1996). Additionally, Swannell et al (2012) interviewed a large representative sample of adults in Australia regarding child abuse-sexual abuse, physical abuse, and neglectnonsuicidal self-injury, dissociation, and self-blame.…”
Section: Gender Abuse History Nonsuicidal Self-injury and Attemptementioning
confidence: 99%
“…Our results also indicated that excess alcohol use was associated with elevated risk of future self-harm hospitalisation, similar to results presented in a prospective study of Australian adults [54]. Still, even though our results do indicate an association, we cannot rule out chance as the explaining factor.…”
Section: Strengths and Limitationssupporting
confidence: 88%
“…AUDIT scores of HSM users were higher than both the general Australian population and other at risk groups (Islam et. al, 2013;Moller et. al, 2013;Smith et.…”
Section: Profile Of Australian Users Of Hsmmentioning
confidence: 99%